Indisputable truth : a new portrait for Katlehong and Thokoza + exchange platform, with the silent power of images - Nzuza, Lindelo (My University, 2018)
1990 was the year Mandela was released from prison, to many mothers it was the year they named their kids Nkululeko (freedom) in anticipation of a new democratic dispensation, but too many in Katlehong and Thokoza in the East Rand, Gauteng, it was the year of violence. Political tension was rough between the supporters of the IFP and the ANC, which resulted in the death of more than 688 people. Photography was extensively used to document the violence. Violence in its nature does not end with a peace truce. Achille Mbembe further notes: violence has the ability to insinuate itself into the economy, domestic life, language, consciousness. It does more than penetrate every space. According to Aida Muluneh, “Photographs have traditionally been regarded as “evidence”, or even as providers of in¬disputable “truth”. And there is little doubt that the present generation reads the world almost exclusively through images. In this age, where images play a significant role in how we read the world, photographs have even more influence” (Jayawardane, 2017). The reality that existed before democracy no longer exist: music, fashion, apartheid rule, many South Africans have achieved their memories in images as evidence and future reference. This research report questions how contemporary architecture can provide a meaningful response to spaces of violence in (Katlehong and Thokoza), using photography. Photography is one of the few occupations that can be mastered without a formal education background and can provide a living wage with a minimum of training and capital investment. This research report proposes an exchange platform which engages with the past and future in creating a civic space in the zone of violence. Developing a learning platform that will contribute to knowledge creation and provide economic opportunities.
This document is submitted in partial fulfilment for the degree: Master of Architecture (Professional) at the University of the Witwatersrand, Johannesburg, South Africa, 2018.